"Nada consta" : implantação, usos e abusos do atestado ideológico no Rio Grande do Sul durante a ditadura civil-Militar (1964 - 1979) - Pereira, Carlos Eduardo da Silva (2022)
This research aims to analyze the certificate of ideology, its implementation at the national level, its specificities in Rio Grande do Sul, the uses of this document by the gaucho repressive apparatus and its extinction during the civil-military dictatorship. The time frame comprises the years 1964 to 1979 and can be divided into three parts. In the first, between 1964 and 1968, we seek to discuss the implementation of the certificate of ideology and the clash between the situation and the opposition raised from the adoption of this document by the civil-military dictatorship and the repressive apparatus. Still in the first cut, we also seek to discuss the implementation of this document within the scope of Rio Grande do Sul and the action of the repressive apparatus of Rio Grande do Sul in the early years of the Dictatorship, understanding this action as part of the implementation of an authoritarian bureaucracy and a favorable context for the expansion of uses of this mechanism. In the second part, between 1969 and 1974, we seek to analyze the influence of post-AI5 repressive legislation on the improvement of the gaucho repressive apparatus and, consequently, on the uses of the certificate of ideology. In addition, we also discussed the ideological certificate as one of the gears that moved the control of the gaucho population, being used in a wide and unrestricted way and promoting a type of repression different from direct and physical, which was aimed at anticipating the actions of the groups considered “subversives” and their isolation, a “preventive” repression. Still in the second part, we also seek to analyze the individual control of the population that was exercised by the Gaucho Department of Political and Social Order through the certificate of ideology and the alternatives used by those affected by this mechanism to find subterfuges in the face of the rejection of this document. In the third part of the time frame, between 1975 and 1979, the objective was to analyze the extinction of the certificate of ideology and its insertion in the debates related to political distension or opening, the Amnesty Law and the return of opposition activities and social movements. Through this research, it was possible not only to discuss the certificate of ideology in the different conjunctures of the Brazilian civil-military dictatorship, the relevance of this document in the plan of national debates between opposition and government and how the preventive face of political repression in Rio Grande do Sul operated.